Service At BBPJN Sumut With The Naive Bayes Method - Lestari, Reni; Elfiandani Nasution, Syahira (Journal of Computer Science and Informatics Engineering, 2023)
SIPINTER (Integrated Public Information Service System) is an online integrated service application for the North Sumatra BBPJN, which is a public service innovation for the North Sumatra National Road Implementation Center including; Licensing Services, BMN Equipment Rental Services, Lab Services. Testing of Construction Materials and Public Communication Implementation Services (PIP and Dumas). The SIPINTER application is an effort by the North Sumatra government to make it easier for its people to process permits, dispensations and recommendations for the use of road sections at the North Sumatra BBPJN without the need to come in person to submit an application as well as access it online via a PC or computer and smartphone. The purpose of this research is to find out how the design of the SIPINTER application can improve BPPJN services in the North Sumatra region. In this study using a qualitative research method with a descriptive analysis approach. In using the SIPINTER application, it shows limitations in mastering technology so that people also have to solve these problems online. In order to encourage the creation of government agency performance accountability as one of the prerequisites for creating a good and trustworthy government, it is necessary to organize a Government Agency Performance Accountability System (SAKIP) that integrates planning, programming, budgeting, and implementation of programs and activities which are then set forth in reports. government agency performance. So that the application of the SIPINTER BPPJN application to the people of North Sumatra needs to be improved. Keywords: SIPINTER Application, Online, BBPJN